The Notional Model of Knowledge Representation - Vykhovanets, V. S. (Journal of physics. Conference series, 2021)
The article describes a model of knowledge, called the notional model. A notion is a thought about a certain unique representation from the subject domain. The notional model uses notion-signs, notion-associations and notion-generalizations that are formed by primary mental abstractions: identification, generalization and association, respectively. The notional model consists of the notional structure and the contents of the notions. The notional structure describes each notion as a set of other notions united by one of the primary mental abstractions. The content of the notion is described using enumerating and resolving procedures. The notional model is semantically invariant, improves the transparency of the subject domain, and allows you to create the knowledge base with a linear estimate of a query execution time.